Utilizing Limited Land for Organic Hydroponic Farming - Zakiya, Firyal Kamilatuz; Rozaki, Zuhud; Wulandari, Retno; Wira Amanah4, Cantika (Universitas Muhammadiyah Yogyakarta, 2024)
This journal article explores the role of the younger generation in shaping the future of Indonesian agriculture. The objective is to assess the level of interest among youth in the agricultural sector and to scrutinize the initiatives undertaken for its advancement. The article refers to prevailing literature in agricultural science, particularly focusing on journals published within the last five years. It accentuates the burgeoning interest of the younger generation in advancing agricultural techniques, including but not limited to hydroponics, aquaponics, aeroponics, and vertiminaponics. Additionally, it emphasizes their proactive engagement in disseminating positive insights about modern agricultural practices within the community.